Small GTP-binding Protein RalA Associates with Weibel-Palade Bodies in Endothelial Cells - de Leeuw, Hubert P. J. C.; Wijers-Koster, Pauline M.; van Mourik, Jan A.; Voorberg, Jan (Thrombosis and Haemostasis, 1999)
In endothelial cells von Willebrand factor (vWF) and P-selectin are stored in dense granules, so-called Weibel-Palade bodies. Upon stimulation of endothelial cells with a variety of agents including thrombin, these organelles fuse with the plasma membrane and release their content. Small GTP-binding proteins have been shown to control release from intracellular storage pools in a number of cells. In this study we have investigated whether small GTP-binding proteins are associated with Weibel-Palade bodies. We isolated Weibel-Palade bodies by centrifugation on two consecutive density gradients of Percoll. The dense fraction in which these subcellular organelles were highly enriched, was analysed by SDS-PAGE followed by GTP overlay. A distinct band with an apparent molecular weight of 28,000 was observed. Two-dimensional gel electrophoresis followed by GTP overlay revealed the presence of a single small GTP-binding protein with an isoelectric point of 7.1. A monoclonal antibody directed against RalA showed reactivity with the small GTP-binding protein present in subcellular fractions that contain Weibel-Palade bodies. The small GTPase RalA was previously identified on dense granules of platelets and on synaptic vesicles in nerve terminals. Our observations suggest that RalA serves a role in regulated exocytosis of Weibel-Palade bodies in endothelial cells.
Keywords: Weibel-Palade bodies; RalA; GTP; von Willebrand factor; endothelial cells